Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1074/jbc.m112.343756
|View full text |Cite
|
Sign up to set email alerts
|

Structure- and Modeling-based Identification of the Adenovirus E4orf4 Binding Site in the Protein Phosphatase 2A B55α Subunit

Abstract: Background:The adenovirus E4orf4 protein must bind protein phosphatase 2A (PP2A) for its functions. Results: The E4orf4 binding site in PP2A was mapped to the ␣1,␣2 helices of the B55␣ subunit. Conclusion: The E4orf4 binding site in PP2A-B55␣ lies above the substrate binding site and does not overlap it. Significance: A novel functional significance was assigned to the ␣1,␣2 helices of the PP2A-B55␣ subunit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…Earlier work indicated that a major target responsible for E4orf4 toxicity in both human and yeast cells is the B55/Cdc55 regulatory subunit of PP2A (6,16,18,(20)(21)(22)(24)(25)(26)(27)(28). Our recent studies indicated that binding of E4orf4 to B55␣ blocks activity against at least some substrates, and we believe that the failure to dephosphorylate critical substrates involved in regulation of the cell cycle causes growth arrest and subsequent cell death (17,53).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Earlier work indicated that a major target responsible for E4orf4 toxicity in both human and yeast cells is the B55/Cdc55 regulatory subunit of PP2A (6,16,18,(20)(21)(22)(24)(25)(26)(27)(28). Our recent studies indicated that binding of E4orf4 to B55␣ blocks activity against at least some substrates, and we believe that the failure to dephosphorylate critical substrates involved in regulation of the cell cycle causes growth arrest and subsequent cell death (17,53).…”
Section: Discussionmentioning
confidence: 86%
“…The E4orf4 polypeptide shares little homology with any known eukaryotic protein; however, two of its major cellular targets have been identified. Events in the nucleus appear to result largely from an interaction with B55 regulatory subunits of protein phosphatase 2A (PP2A) (6,(16)(17)(18)(19)(20)(21)(22) that we have shown in the case of B55␣ blocks the activity of PP2A against at least some substrates (17,53). E4orf4 is also toxic in yeast (Saccharomyces cerevisiae), and this effect is largely abrogated in yeast lacking CDC55, the B55 ortholog (22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 86%
“…PP2A functions vary extensively (40)(41)(42)(43)(44)(45), due in large part to the 15 or so mammalian B subunits, which have been divided into three structurally divergent classes, designated B/B55, B=/B56, and BЉ, as well as Bٞ striatin/SG2NA (42,46). Our group found that E4orf4 interacts solely with the B/B55 family (14), and more recent studies showed that E4orf4 associates with the B55␣ subunit in a region believed to be involved in substrate binding (1,35). Moreover, we have proposed that E4orf4 acts much like an inhibitory pseudosubstrate for PP2A B55␣ when expressed at high levels, preventing interactions with and dephosphorylation of substrates such as p107 (1) and inducing cell death by preventing dephosphorylation of key substrates required for cell viability (6,14).…”
mentioning
confidence: 94%
“…Moreover, we have proposed that E4orf4 acts much like an inhibitory pseudosubstrate for PP2A B55␣ when expressed at high levels, preventing interactions with and dephosphorylation of substrates such as p107 (1) and inducing cell death by preventing dephosphorylation of key substrates required for cell viability (6,14). Previous studies by our group and others indicated that such binding to B55 PP2A subunits is essential for E4orf4 toxicity (16,26,34,35), as E4orf4 mutants that are defective in B55␣ binding (we refer to them as class I mutants) also are defective in cell killing (10). However, members of another class of E4orf4 mutants exist that also are defective for cell killing, even though they bind high levels of B55␣ (10) (we refer to these as class II mutants), suggesting that B55␣ binding is necessary but not sufficient for E4orf4 toxicity and that other essential targets exist.…”
mentioning
confidence: 99%
“…Nevertheless, E4orf4 expression also rapidly resulted in cell rounding, a hallmark of early mitosis, suggesting that E4orf4 might induce early mitotic events but create problems with normal passage through and exit from mitosis. In this context, it should be remembered that E4orf4 was shown to bind to the putative substrate binding groove of the B55 regulatory subunit of PP2A (7,21), thus inhibiting PP2A B55 activity by interfering with the access of substrates to the holoenzyme (7,9). Interestingly, such inhibition may mimic a natural process for entry into mitosis regulated by Greatwall (Gwl) and endosulfine alpha (ENSA), which are involved in the control and timing of M phase (22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%